Germline de novo alterations of RUNX1T1 in individuals with neurodevelopmental and congenital anomalies - Erfan Aref-Eshghi; Katherine J. Anderson; Lauren Boulay; Kathleen Brown; Jessica Duis; Christine A. Giummo; Jessica Ogawa; Deanna Alexis Carere; Elizabeth A. Normand; Yaping Qian; Kirsty McWalter; Erin Torti (HGG Advances)
Summary: Runt-related transcription factor 1 translocated to 1 (RUNX1T1; also known as eight-twenty-one [ETO]) encodes a transcription regulator for hematopoietic genes and is well known for its involvement in hematologic malignancies, particularly acute myeloid leukemia (AML). However, its role in congenital disease is less understood. This study provides detailed clinical and molecular information on three cases exhibiting neurodevelopmental and congenital anomalies with germline de novo alterations in RUNX1T1. One case features a de novo nonsense variant in the 5′ region of the gene (c.106C>T p.Gln36Ter), while the other two harbor de novo missense variants in the C terminus end (c.1234G>A p.Gly412Arg and c.1561C>T p.His521Tyr). Common features across cases include craniofacial dysmorphism and neurodevelopmental issues, including developmental delay, learning disabilities, attention-deficit hyperactivity disorder, and autism. This study, in conjunction with previously reported germline disruptions of RUNX1T1, provides evidence supporting the role of germline RUNX1T1 variation in human congenital neurodevelopmental disorders.